A subset of image‐defined risk factors predict completeness of resection in children with high‐risk neuroblastoma: An international multicenter study - Espinoza, Andres F.; Bagatell, Rochelle; McHugh, Kieran; Naranjo, Arlene H.; Van Ryn, Collin; Rojas, Yesenia; Lyons, Karen; Guillerman, R. Paul; Kirby, Chaim; Brock, Penelope; Volchenboum, Samuel; Simon, Thorsten; et al. (Pediatric blood & cancer, 2024)
Background Image‐defined risk factors (IDRFs) were promulgated for predicting the feasibility and safety of complete primary tumor resection in children with neuroblastoma (NB). There is limited understanding of the impact of individual IDRFs on resectability of the primary tumor or patient outcomes. A multicenter database of patients with high‐risk NB was interrogated to answer this question. Design/methods Patients with high‐risk NB (age <20 years) were eligible if cross‐sectional imaging was performed at least twice prior to resection. IDRFs and primary tumor measurements were recorded for each imaging study. Extent of resection was determined from operative reports. Results There were 211 of 229 patients with IDRFs at diagnosis, and 171 patients with IDRFs present pre‐surgery. A ≥90% resection was significantly more likely in the absence of tumor invading or encasing the porta hepatis, hepatoduodenal ligament, superior mesenteric artery (SMA), renal pedicles, abdominal aorta/inferior vena cava (IVC), iliac vessels, and/or diaphragm at diagnosis or an overlapping subset of IDRFs (except diaphragm) at pre‐surgery. There were no significant differences in event‐free survival (EFS) and overall survival (OS) when patients were stratified by the presence versus absence of any IDRF either at diagnosis or pre‐surgery. Conclusion Two distinct but overlapping subsets of IDRFs present either at diagnosis or after induction chemotherapy significantly influence the probability of a complete resection in children with high‐risk NB. The presence of IDRFs was not associated with significant differences in OS or EFS in this cohort.